Effects of Hibiscus sabdariffa Linn. on insulin-like growth factor binding protein 3 (IGFBP-3) to prevent overtraining syndrome (Medical Journal of Indonesia, 2014)
Background: Excessive physical exercises (overtraining) can increase the production of reactive oxygen species (ROS). One of the indicators of overtraining syndrome is a decrease in insulin-like growth factor binding protein 3 (IGFBP-3). Administration of Hibiscus sabdariffa Linn., a powerful antioxidant, is expected to boost endogenous antioxidants, and thus prevents overtraining. The aim of this study is to determine the effect of H. sabdariffa on IGFBP-3 levels in rats under "overtraining physical excersice". Methods: This experimental study was conducted on 30 male rats (Rattus norvegicus 200-250 grams), randomly allocated into 5 groups: 1) control group (C); 2) control with H. sabdariffa (C-Hib); 3) mild aerobic exercise (A-Ex); 4) overtraining exercise (OT); 5) overtraining exercise with H. Sabdariffa (OT-Hib). H. sabdariffa (400 mg/kg/d, 11 weeks) were administered orally via syringe cannula. IGFBP-3 was measured by using ELISA (Cusa bio kit) and data were analyzed with ANOVA test. Results: Plasma level of IGFBP-3 in the C and OT groups were 17.4 ± 10 mIU/L, the lowest in OT groups (10.7 ± 9.9 mIU/L) and the OT-Hib group had the highest level (31.5 ± 6.2 mIU/L). There was significant difference of the level IGFBP-3 in OT groups with A-Ex groups (10.7 ± 9.9 vs 23.5 ± 9.7 mIU/L; p < 0,05). The significant difference was also observed in the level of IGFBP 3 between C groups and the OT-Hib groups (17.4 ± 10 vs 31.5 ± 6.2; p < 0.05). Conclusion: Administration of H. sabdariffa can prevent the decrease of IGFBP-3 levels in overtraining rats, indicating its role in preventing overtraining syndrome.